Pengembangan Media Pembelajaran Virtual Reality Materi Sistem Pencernaan Manusia di SMP - Maulana, M.Rizky; Ismanto, Edi; Novalia, Melly (Computer Science and Information Technology, 2025)
The use of virtual reality (VR) technology is one of the innovative approaches in the development of learning media. This technology is able to present more real and interactive visualizations so that it makes it easier to understand complex materials such as the human digestive system and abstract concepts in science lessons. The use of technology-based media such as VR is important so that teachers and students can keep up with the times and take advantage of technological advances in the teaching and learning process, especially at SMP Muhammadiyah 1 Pekanbaru. This research aims to design and develop virtual reality-based learning media on human digestive system materials for grade VIII junior high school students. The research was conducted using the Research and Development (R&D) method using a 4D model which includes the stages of define, design, develop, and disseminate. The media developed has been validated by media experts and material experts, and tested on students. The results of the study showed excellent quality with a feasibility rate of 98% from media experts, 96% from material experts, and 93% from students. Thus, the virtual reality-based learning media developed was declared valid, very feasible, and effective to support the learning of digestive system materials.